Physiological responses to variations in grazing and light conditions in native and invasive fucoids. (August 2018) - Olabarria, Celia; Arenas, Francisco; Fernández, Ángela; Troncoso, Jesús S.; Martínez, Brezo
Abstract: Poor physiological acclimatization to climate change has led to shifts in the distributional ranges of various species and to biodiversity loss. However, evidence also suggests the relevance of non-climatic physical factors, such as light, and biotic factors, which may act in interactive or additive way. We used a mechanistic approach to evaluate the ecophysiological responses of four seaweed species (three dominant intertidal fucoids, Fucus serratus, Ascophyllum nodosum, Bifurcaria bifurcata, and the invasive Sargassum muticum ) to different conditions of grazing, light irradiance and ultraviolet (UV) radiation. We performed a large-scale mesocosm experiment with a total of 800 individual thalli of macroalgae. The factorial experimental design included major algal traits, photoacclimation, nutrient stoichiometry and chemical defence as response variables. Few significant effects of the factors acting alone or in combination were observed, suggesting a good capacity for acclimatization in all four species. The significant effects were generally additive and there were no potentially deleterious synergistic effects between factors. Fucus serratus, a species currently undergoing a drastic contraction of its southern distribution limit in Europe, was the most strongly affected species, showing overall lower photosynthetic efficiency than the other species. The growth rate of F. serratus decreased when UV radiation was filtered out, but only in the presence of grazers. Moreover, more individuals of this species tended to reach maturity in the absence of grazers, and the nitrogen content of tissues decreased under full-spectrum light. Only the phlorotannin content of tissues of B. bifurcata and of exudates of A. nodosum, both slow-growing species, were positively affected by respectively removal of UVB radiation and the presence of grazers. The findings for S. muticum, a well-established invasive seaweed across European coasts, suggested similar physiological response of this fast-growing species to different levels of grazing activity and light quality/intensity. As expected, this species grew faster than the other species. Bifurcaria bifurcata and A. nodosum only showed minor effects of light quality and grazing on phlorotannins content, which suggests good resistance of these two long-lived species to the experimental conditions. Mechanistic approaches that are designed to analyse interactive effects of physical and biotic factors provide an understanding of physiological responses of species and help to improve the confidence of predictive distribution models. Highlights: Effects of grazing and irradiance on ecophysiological traits of four fucoids were assessed. Data suggest divergent growth rates and eco-physiological strategies for the four species. When significant, the effects on ecophysiological traits were mainly additive. F. serratus, which suffers a drastic retraction in northern Spain, was the most impacted species.